UJI AKTIVITAS SERBUK JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq.) P.Kumm) TERHADAP KADAR GLUKOSA DARAH PADA MODEL HEWAN HIPERKOLESTEROLEMIA-DIABETES - Dwinthasari Meilinda Azhari; Yuliet Yuliet; Khildah Khaerati (Universitas Tadulako, 2016)
Research on the activity of white oyster mushroom powder (Pleurotus ostreatus (Jacq.) P.Kumm) against blood glucose levels in animal model of hypercholesterolemia-diabeties has been conducted. This research aimed to determine its activity as well as its effective dose in lowering blood glucose levels. A number of laboratory rats were divided into five groups and each group consisted of four rats. The 1st group (negative control) was given 0.5% suspension of Na-CMC; the 2nd and 3rd group (positive controls) were respectively given 0.45 mg/kgBW of Glibenclamide and 45 mg/KgBW of Metformin; while each of the 4th, 5th, and 6th groups was given the powder as much as of 250, 500 and 750 mg/kgBW. On day 1 to day 14, they were fed with high cholesterol food then induced with 30 mg/kgBW of streptozotocin, and on day 17 were treated with suspension of white oyster mushroom powder. On day 24 and day 31, the blood glucose levels were checked. Data of blood glucose levels difference between before and after treatment were calculated and statistically processed of which normality had been previously tested using Shapiro Wilk and homogeneity using Levene Test. Data that had normal distribution were statistically analyzed using ANOVA (analysis of variance) with 95% confidence interval and continued with Post hoc Duncan to see the differences among the groups which were significantly different. While, data that did not have normal distribution were analyzed using non-parametric statistics, Kruskal Wallis Test, and then further using Mann Whitney Test. The results showed that powder of white oyster mushroom had antidiabetic activity at effective dose of 250 mg/KgBW